Budding success and growth aptitude under rainfed conditions during the first year of plantation: Comparison between Pistacia terebinthus L. and UCB-I - Memmi H.; Couceiro J.F.; Gijón M.C.; Pérez-López D. (XVI GREMPA Meeting on Almonds and Pistachios, 2016)
In Spain, pistachio area was negligible in the 1990’s, nowadays, it is estimated to 6,000 hectares. However, one of the most important issues that created doubt among farmers for its introduction has been the choice of rootstock. The most used rootstocks in the world are Pistacia atlantica, Pistacia integerrima, Pistacia terebinthus and UCB-I. Pistacia terebinthus is a native Spanish forests rootstock known for its adaptation to the lands of the Iberian Peninsula. However, it is also known for its small vigor and its low tolerance to some diseases like Verticilium dahliae. In contrast, UCB-I, a hybrid between Pistacia integerrima and Pistacia atlantica is a rootstock known for its high vigor, its tolerance to Verticillium dahliae and its high yields, however, its behavior is unknown under rain-fed conditions. For this purpose, as a first step, a Split-plot trial comparing these two rootstocks with different cultivars under rain-fed conditions was implemented in Castilla-La-Mancha (Spain). The primary objective was to assess the aptitude of budding success and the difference in the vegetative growth of these two rootstocks under rain-fed conditions. Rootstock diameter, scion diameter, the percentage of budding success and the length of resulted scions were measured. The results showed that UCBI had a higher percentage of budding success (70% vs. 54%), a significantly higher rootstock and scion diameters (25 mm vs 15 mm for rootstock and 22 mm vs 15 mm for scion). However there was no difference between lengths of sprouted buds. Also, there was no influence of the variety in relation to these parameters.
16. Meeting of GREMPA (Groupe de Recherches Méditerranéennes pour l\'Amandier et Pistachier / Mediterranean Research Group for Almond and Pistachio), 2015/05/12-14, Meknes (Morocco)